Influence of Pressure on Occurrence of Occupational Fraud Loss in Public Secondary Schools in Nairobi County, Kenya - Limo, Silas Kiprop; Gathoni, Benson; Kimungunyi, Sammy (Journal of Public Policy and Administration, 2025)
Purpose: The purpose of this study was to determine the influence of pressure on occurrence of occupational fraud loss in public secondary schools in Nairobi County, Kenya. Methodology: The study adopted a positive paradigm with a descriptive design which targeted a sample of 101 public secondary schools in Nairobi County. An audit team leader from the government was the respondent for each school. Fishers sampling formulae was used to get a sample of 96 respondents. Stratified random sampling was used to ensure that all sub-counties were fairly represented in the sample. Primary data was used in this study through the administration of a semi-structured questionnaire. data collected was analyzed using the statistical package for social sciences software (SPSS) version 21, using the linear regression analysis. The results collected were presented in form of descriptive statistics, that is, mean and standard deviation in tables, charts and figures. Findings: The study found that occupational fraud loss in public secondary schools is significantly influenced by pressure (β = 0.324; p<0.05). Unique Contribution to Theory, Practice and Policy: The study was guided by Donald Cressey’s theory of the fraud triangle. In terms of practice, school administrations should focus on fostering an ethical work environment that minimizes financial pressure on employees while limiting opportunities for fraudulent behavior.